Improvement of Time Complexity on External Sorting using Refined Approach and Data Preprocessing - Hrushikesava Raju, S; Nagabhusana Rao, M (International Journal of Computer Sciences and Engineering, 2025)
Generally, huge data of any organization possess data redundancy, noise and data inconsistency. To eliminate, Data preprocessing should be performed on raw data, then sorting technique is applied on it. Data preprocessing includes many methods such as data cleaning, data integration, data transformation and data reduction. Depending on the complexity of given data, these methods are taken and applied on raw data in order to produce quality of data. Then, external sorting is applied. The proposed external sorting now takes the number of passes less than actual passes log B (N/M) + 1 for the traditional B – way external merge sorting. Also, the number of Input / Outputs of proposed method is less than 2*N* (log B (N/M) + 1) of Input / Outputs than traditional method, and also proposed method consume least number of runs compared to actual basic external sorting.